The Effect of Motivation, Creativity, and Employee Behavior on Generation Z Employee Performance - Agustina, Mei Anggraeni; Febrian, Wenny Desty (Siber International Journal of Digital Business (SIJDB), 2025)
This study aims to analyze the influence of motivation, creativity, and work behavior on the performance of Generation Z employees. Generation Z is known for its unique characteristics, such as high creativity and an entrepreneurial spirit, but also faces challenges in maintaining work consistency. This research employs a quantitative approach using a survey method involving Generation Z employees at PT. XYZ. The analyzed variables include work motivation (intrinsic and extrinsic drive), creativity (the ability to think innovatively and generate new solutions), and work behavior (discipline, initiative, and efficiency). Employee performance is measured based on quantity, quality, and timeliness in task completion. The findings reveal that motivation, creativity, and work behavior positively and significantly affect the performance of Generation Z employees. Work motivation is the primary factor driving employee productivity, followed by creativity, which contributes to increased innovation in task execution. Additionally, good work behavior, such as discipline and initiative, also positively impacts work effectiveness. These results provide insights for organizations in developing more effective employee management strategies to enhance overall organizational performance.